Bioinformatics approach based research of profile protein carbonic anhydrase II analysis as a potential candidate cause autism for the variation of learning subjects biotechnology - Dian Eka A. F. Ningrum; Mohamad Amin; Betty Lukiati (JPBI (Jurnal Pendidikan Biologi Indonesia), 2017)
This study aims to determine the needs of learning variations on Biotechnology courses using bioinformatics approaches. One example of applied use of bioinformatics in biotechnology course is the analysis of protein profiles carbonic anhydrase II as a potential cause of autism candidate. This research is a qualitative descriptive study consisted of two phases. The first phase of the data obtained from observations of learning, student questionnaires, and questionnaires lecturer. Results from the first phase, namely the need for variations learning in Biotechnology course using bioinformatics. Collecting data on the second stage uses three webserver to predict the target protein and scientific articles. Visualization of proteins using PyMOL software. 3 based webserver which is used, the candidate of target proteins associated with autism is carbonic anhydrase II. The survey results revealed that the protein carbonic anhydrase II as a potential candidate for the cause of autism classified metaloenzim are able to bind with heavy metals. The content of heavy metals in autistic patients high that affect metabolism. This prediction of protein candidate cause autism is applied use to solve the problem in society, so that can achieve the learning outcome in biotechnology course.